An exploratory study on the insecticidal potential of various chemical agents against Bactrocera cucurbitae: Potential of selected insecticides against Bactrocera cucurbitae (Zoo Botanica, 2025)
Bactrocera cucurbitae is the most destructive species of fruit fly. It is a serious pest of several fruits in South Asian nations like as Pakistan, India, and Malaysia. During these studies, toxicity of fipronil, spinosad, emamectin-benzoate, bifenthrin, cypermethrin and deltamethrin was observed by two different methods i.e., diet incorporate method and contact method against laboratory reared population of B. cucurbitae. The culture was reared at 28±2°C temperature with 65±5% relative humidity and 12:12 (D/L) photoperiod in the laboratory. According to the results in diet incorporate method; spinosad was found as the most efficient insecticide against B. cucurbitae as it showed the least LC50 i.e., 2.86 after 72 hours. It was followed by emamactin-benzoate. The LC50 value of emamectin-benzoate was 2.98 after 72 hours against B. cucurbitae. The third most efficient LC50 was 4.95 of spinosad after 48 hours. According to the results in contact method; cypermethrin was found as most efficient insecticide against the B. cucurbitae as it showed least LC50 i.e., 0.62 after 72 hours. It was followed by insecticide of the same group, i.e., bifenthrin. The LC50 value of bifenthrin was 0.63 after 72 hours against B. cucurbitae and the third most efficient insecticide was deltamethrin which had 1.06 LC50 values after 72 hours. Hence, the results showed that LC50 values of contact method were lower than diet incorporate method; so it is the most efficient method to control melon fruit fly among the two tested methods and cypermethrin is the most effective insecticide.
Keywords: Toxicity; Bactrocera cucurbitae; contact method; diet incorporate method